2018
DOI: 10.1016/j.jocm.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the anchoring bias in multiple question CV surveys

Abstract: The elicitation format is a crucial aspect of Contingent Valuation (CV) surveys and can impact their reliability. This paper contributes to the extensive debate on WTP (Willingness To Pay) elicitation formats by assessing whether the Circular Payment Card (CPC) can reduce anchoring on respondents' previous answers under multiple elicitation questions. This new format uses a visual pie-chart representation without start or end points: respondents spin the circular card in any direction until they find the secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…There had been numerous and consistent evidence for anchoring bias, which seems to depend strongly from elicitation format. For instance, Champenois et al (2018) showed that in the case of a contingent valuation survey, a circular payment card reduces anchoring compared to the standard one (closed-ended formats). Our results showed that, even with an open-ended format as ours, individual bids to obtain the nuisance reduction, that should avoid anchoring coming from numerical cue, we have obtained some endogenous anchoring bias.…”
Section: Discussionmentioning
confidence: 99%
“…There had been numerous and consistent evidence for anchoring bias, which seems to depend strongly from elicitation format. For instance, Champenois et al (2018) showed that in the case of a contingent valuation survey, a circular payment card reduces anchoring compared to the standard one (closed-ended formats). Our results showed that, even with an open-ended format as ours, individual bids to obtain the nuisance reduction, that should avoid anchoring coming from numerical cue, we have obtained some endogenous anchoring bias.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for employing these three elicitation techniques stems from the fact that the information collected on the respondents' WTP tend to be affected by the format of these techniques. Comparisons between the results obtained from these three elicitation techniques have been carefully examined in two companion papers 29,30 . Finally, the questionnaire gathered information on the respondents' socio‐economic, socio‐demographic and health characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…If respondents were not willing to join, they were then asked to state the reason(s) and whether they would join the scheme if it was offered for free or at a Three different elicitation techniques were employed to gather information on respondents' WTP values: the well-known Open-Ended (OE) and Payment Card (PC) techniques, 27,28 and a variant known as the Circular Payment Card (CPC). 29,30 The CPC uses a visual representation of a circular card with no pre-determined start or end points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They underscore the importance of being aware of how initial information or personal experiences can serve as anchors, potentially leading to biased adjustments and decisions. Champonnois et al (2018) tested the potential of different survey formats to mitigate the anchoring effect, revealing how various formats can influence participants' decision-making processes. This study emphasizes the impact of presentation and context on reducing cognitive biases.…”
Section: Anchoring and Adjustment Biasmentioning
confidence: 99%